Ameliorative effect of allopurinol on cisplatin-induced memory impairment in male Wistar rat: Ameliorative effect of allopurinol on cisplatin-induced memory impairment - Masoud Hosseinzadeh; Samad Nazemi; Omid Gholami; Marzieh Kafami; Mohammad Keyvanloo Shahrestanaki; Akbar Peghhan (Iranian Journal of Pharmaceutical Sciences, 2022)
Neurotoxicity is an adverse effect of chemotherapy drugs on the central nervous system. Many studies have demonstrated that xanthine oxidase inhibitors prevent the formation of reactive oxygen species (ROS). The present study aimed to investigate the effects of allopurinol as an oxidase inhibitor on the learning and memory impairment induced by cisplatin. This study was conducted on 40 male Wistar rats, which were randomly divided into five groups, as follows: 1) control injected with saline (1 ml/kg/i.p); 2) cisplatin (5 mg/kg/once a week; i.p.); 3) allopurinol (ALP; 50 mg/kg/once a week; P.O.); 4) Cis+ALP 50 (cisplatin 5 mg/kg/i.p and allopurinol 50 mg/kg/once a week; P.O.) and 5) Cis+ALP 100 (cisplatin 5 mg/kg/i.p and allopurinol 100 mg/kg/once a week; P.O.). Drugs were administered for five weeks in all groups. The interval between administrations of drugs were half an hour. Morris water maze (MWM) was used to evaluate the memory and learning of the animals. The tissue brain concentrations of malondialdehyde (MDA), thiol, and superoxide dismutase (SOD) were measured using biochemical tests. According to the results, the cisplatin group had longer escape latency and shorter time spent and traveled pathway in the target quadrant compared to the control group. On the other hand, allopurinol treatment significantly reversed the results of the spatial memory test. The biochemical data indicated that cisplatin increased MDA concentration but decreased thiol and SOD activity compared to the control group. Administration of allopurinol decreased the MDA level but increased the thiol levels in the cortex and hippocampus tissues. Therefore, it was concluded that allopurinol could improve cisplatin-induced memory impairment by affecting the oxidative status of the brain tissue.